Aplicación móvil integrando un Chatbot para la oferta de servicios de vivienda, alimentación y entretenimiento para los estudiantes de la Universidad Nacional de Chimborazo - Medina Villacres, Wellington Asdrubal (2022)
In the vicinity of the Universidad Nacional de Chimborazo there are different rental, food and entertainment services that students do not know about, as they come from other provinces or do not belong to the city of Riobamba, generating a problem when looking for these services, as there is scattered information. This is why the providers do not obtain a benefit and opportunity for the majority of the students to know about the services they offer. To solve this problem, the following project explains the development and implementation of a mobile application integrating a Chatbot made through Android Studio using JAVA language, which will be dynamic, easy to use and can only be used on mobile devices with Android operating system. For the development of this application began with a planning supported by the Scrum methodology and this served to have a good management when developing the application as it helps to have a coordination for the development of this project; also used the database consumption, the Maps api to obtain the geolocation within the application and the Chatbot was integrated internally programmed obtaining permissions from Google voice recognition. The mobile application that was developed is called UForáneo and its purpose is to allow only students or members of the Universidad Nacional de Chimborazo to obtain relevant information about the services near the institution since within the application you can see the leases, food and entertainment surrounding of university and each section provides unique information in detail showing pictures, description, details, exact location, a button to contact the provider of each service and the Chatbot so that users can have a chat with the artificial intelligence integrated in the application and learn about the benefits that exist in each section. To conclude the project, once the creation of the UForáneo application had been completed, a survey was carried out among the students of the Information Technologies degree course to evaluate the satisfaction and performance efficiency of the mobile application, showing that the result obtained was satisfactory when using the application.